Proyecto de factibilidad para la creación de un centro de desarrollo empresarial para lograr un fortalecimiento de las Mypes de la ciudad de Yantzaza, provincia de Zamora Chinchipe - Simancas Aguilar, Magaly Edith (2014)
This academic paper entitled " PROYECT STUDY FOR THE ESTABLISHMENT OF A BUSINESS DEVELOPMENT CENTER FOR STRENGTHENING IN ACHIEVING MYPES Yantzaza CITY , PROVINCE DE ZAMORA CHINCHIPE " raised the general objective : To develop a feasibility study for implementation of a business development center for a building in the city MYPES Yantzaza . To fulfill this objective it was necessary to raise the following specific objectives: Perform a market survey to determine the current supply, current and potential demand for the operation of a Business Development Center; Conduct administrative and technical study for the location of the consulting firm, to determine the location, size, engineered, installed and used the project capacity; Design the organizational, operational and legal structure of the Business Development Center; and, Prepare the financial study that contains general investment plan, budget revenue and expenditure and financial evaluation ( NPV, IRR , B / C , PRC , Sensitivity Analysis , ETC ). Where was determined that currently there is no one that offers the service that this project aims to offer company. Besides the potential demand in the city is 875 Yantzaza mypes with growth of 6%. Also a real demand of 83.27 % , where the actual demand turned out to be 93.45 % , e 681 mypes would be willing to hire the service of this project was obtained . Could This study will determine the optimal location of the company should be in the , Main Avenue and Calle Luis Bastidas , opposite the central park of the city of Yantzaza . Also the size of the company was made based on the installed capacity , which was determined to cover 16.95% of the unmet demand equivalent to 133 mypes . Which will start using 70 % and will increase by 3% annually to reach 97% of the installed capacity. The organizational structure responds to a vertical authority where different departments that worked in the company are detailed. Structural, Functional and Positional flowchart is described. Similarly in the function manual positions, functions, and requirements to be fulfilled by every human talent within the organization are defined. This point is also defined that gives the company philosophy, it is formulated based on the reason for the company and its growth forecast for the 10 year life of the project. This study found that investment required is $ 17,223.05 to be funded with 41.94 % by the investor and 58.06 % by a financial institution in the amount of $ 10,000 within 24 months and interest rates of 11.83%. Annual revenues are estimated at $ 64.756,37 at a price of $ 486.89 that contains a profit margin of 20%, which means $ 15.22 when counseling or training. In calculating the financial indicators, the following results were obtained: Opportunity cost 17.75% ; project NPV $ 28,915.16 , the cost benefit ratio of 1.20, capital recovery period would occur in three years , seven months and 13 days , the project IRR is 47.99% . Similarly, the project is able to accept a increment0 cost of 7.90% and a decrease in revenue of 6.59%. With this background and once demonstrated through market research that there is unmet and existing feasibility study financial and economic performance we recommend investing in this project demandad.